Informativity of proteinograms as a clinical-diagnostic test at dispoteinemia in the age aspect - Yeriomenko, R. F.; Ostapets, M. O. (Journal of Education, Health and Sport, 2017)
The article analyzed dates of the usefulness of proteinograms as a clinical diagnostic test at dysproteinemia in age aspect. Established that proteinograms has differences that depending on age, so these aspects should be considered in the diagnosis of certain pathological conditions in different age groups. Studying of children’s proteinograms in various pathological conditions indicates the appropriate changes in the fractional part of albumin and globulin, that characterized the development of inflammation and destruction of connective tissue. Besides diagnostic tests that help in the diagnosis, determine the stage of disease and the effectiveness of therapy is to study proteins "acute phase" and rheumatoid factor. Established the feasibility of proteinograms on the studying of dysproteinemia in different pathological conditions in adult age. It is found correlation between changes in protein fractions and stage of pathological process in connective tissue diseases (rheumatoid arthritis and systemic lupus erythema). At skin diseases, urinary, respiratory and hepatobiliary systems were recorded proteinograms changes depending on the damage of a system. Analysis of the results allows more accurate founded the diagnosis, determine the stage of the pathological process and evaluate the effectiveness of the pharmacotherapy.